Immunization status of children in the age group 0-5 years in urban slum area of Pratiksha nagar, Sion, Mumbai - Kadam, Deepali Mohan; D’souza, Chiara; Sagwekar, Pranali V.; Patel, Khadija (International Journal of Research in Medical Sciences, 2017)
Background: In India, immunization services are being provided through existing healthcare delivery system. In spite of services being available, it is observed that many children are not immunized till date. This study was carried out with the aim to find the immunisation status of the children in the urban slum areas of Pratiksha nagar, Sion which is the field practice area of Department of Community Medicine, K. J. Somaiya Medical College and Reasearch Centre. Objectives of the study was to assess the proportion of children fully immunized, to assess the proportion of children partially immunized, to assess the proportion of children not at all immunized and to explore the reasons for partial immunization. Methods: It is a cross-sectional study. This study was carried out in urban slum areas of Pratiksha nagar, in Sion namely Almeda compound, Shastrinagar B wing, Panchsheel nagar which are the field practice areas of Department of Community Medicine located in F north ward of Mumbai city. Results: 148 (76.29%) children were fully immunized and 46 (23.71%) were partially immunized. Out of the 46 children who were partially immunized, 23.91% respondents reported that child was ill when immunisation was due, so they did not take the child to health care facility for immunisation, followed by the other common reason that family was out of town (17.39%). Conclusions: The study highlights the need for educating parents that minor illnesses are not a contraindication for immunisation and that the child may receive the vaccine due in any health centre when they are out of town so as to avoid delay between the doses therein not interrupting the immunisation schedule.